2012
DOI: 10.1007/s12098-011-0618-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Kearns Sayre Syndrome—Case Report with Review of Literature

Abstract: Kearns-Sayre Syndrome is form of rare mitochondrial cytopathy, first described by Thomas P. Kearns and George Pomeroy Sayre in 1958 and is characterized by progressive external opthalmoplegia, cardiac conduction block, pigmentary retinal degeneration, variable number of red ragged fibers on muscle biopsy. It presents before the child reaches the age of twenty. Kearns-Sayre syndrome may affect many organ systems and additional features may include myopathy, dystonia, bulbar symptoms in the form of dysarthria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
6
1
1
Order By: Relevance
“…[ 16 ] In the present study, however, only five KSS patients (26.3%) had hearing loss, much lower than the incidence of 64.0% in Japanese patients,[ 13 ] suggesting thorough auditory function evaluation is needed in these KSS patients to detect subclinical hearing loss in the future. Proximal muscle weakness was reported in some KSS patients in other studies,[ 4 17 ] but it was not common in our patients. Follow-up showed that the greatest impairments affecting KSS patients were cerebellar signs and heart problems.…”
Section: Discussioncontrasting
confidence: 62%
“…[ 16 ] In the present study, however, only five KSS patients (26.3%) had hearing loss, much lower than the incidence of 64.0% in Japanese patients,[ 13 ] suggesting thorough auditory function evaluation is needed in these KSS patients to detect subclinical hearing loss in the future. Proximal muscle weakness was reported in some KSS patients in other studies,[ 4 17 ] but it was not common in our patients. Follow-up showed that the greatest impairments affecting KSS patients were cerebellar signs and heart problems.…”
Section: Discussioncontrasting
confidence: 62%
“…Brain MRI usually shows large lobe lesions, brain atrophy with or without basal ganglia calcification. In contrast, myoclonus epilepsy, heart block (WPW), pigmentary retinopathy, sensorineural hearing loss, premature graying pigmentary retinopathy, partial heart block, and diffuse white matter MRI alterations are features of the KSS syndrome [3] . Cerebellar ataxia is common in both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…MELAS syndrome is commonly associated with an A to G transition at nt 3243 of the mtDNA. In contrast, KSS is a mitochondrial disorder characterized by the early-aged onset of progressive external ophthalmoplegia or pigmentary retinopathy, together with at least one of a triad of cerebellar ataxia, heart block and elevated cerebrospinal fluid protein [3] . Typically, KSS is due to single large-scale mtDNA deletions and is almost always sporadic.…”
Section: Introductionmentioning
confidence: 99%
“…As in other mitochondrial disorders, this syndrome is inherited exclusively through the maternal line, because all mitochondria in the zygote are maternal in origin [40]. The clinical presentation of KSS is determined by the degree of muscular involvement, and in most patients, onset is between 15 and 20 years of age [41][42][43].…”
Section: Diseases Associated With Disturbances In Energy Required Formentioning
confidence: 99%